Neurodevelopmental continuum and pathogenic CNV detection in adult onset psychiatric disorders: microarray analysis in psychiatric clinical practice - Á. Ruiz De Pellón Santamaría (European Psychiatry, 2022)
Introduction Structural variations of DNA, such as copy number variations (CNVs), are important contributors to risk for human diseases. Several CNVs have been associated with an increased risk of early-onset neurodevelopmental disorders (NDD), adult-onset psychiatry disorders and physical comorbidities. While in Pediatrics the microarray is the first-line genetic analysis technique in the study of child onset NDD, its use in psychiatry care of young/adult onset NDD has been limited to research purposes.